1998
DOI: 10.1038/sj.onc.1201630
|View full text |Cite
|
Sign up to set email alerts
|

CpG methylation within the 5′ regulatory region of the BRCA1 gene is tumor specific and includes a putative CREB binding site

Abstract: Breast cancer is a genetic disease arising from a series of germ-line and/or somatic DNA changes in a variety of genes, including BRCA1 and BRCA2. DNA modi®ca-tions have been shown to occur by a number of mechanisms that include DNA methylation. In some cases, the aberrant methylation of CpGs within 5' regulatory regions has led to suppression of gene activity. In this report we describe a variation in the pattern of DNA methylation within the regulatory region of the BRCA1 gene. We found no evidence of methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
160
0
2

Year Published

1999
1999
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 175 publications
(167 citation statements)
references
References 20 publications
5
160
0
2
Order By: Relevance
“…Our laboratory (Mancini et al, 1998) and others have previously shown site-speci®c e ects of DNA methylation within the promoter regions of a variety of tumour suppressor genes. However, similar information concerning the NF1 gene has been lacking.…”
Section: Methylation and Creb Bindingmentioning
confidence: 79%
See 4 more Smart Citations
“…Our laboratory (Mancini et al, 1998) and others have previously shown site-speci®c e ects of DNA methylation within the promoter regions of a variety of tumour suppressor genes. However, similar information concerning the NF1 gene has been lacking.…”
Section: Methylation and Creb Bindingmentioning
confidence: 79%
“…For example, methylation of exonic CpGs is considered to be a major contributor to point mutations due to the hypermutability of 5-methylcytosine. In fact, up to 30% of germ-line mutations leading to human genetic disease occur as C to T transitions at CpG dinucleotides which frequently result in protein truncating mutations (Mancini et al, , 1998Rodenhiser et al, 1997;Cooper and Krawczak, 1989). DNA methylation within gene regulatory regions, on the other hand, may mediate gene inactivation either by causing general alterations in chromatin con®guration or by interfering with the binding of transcription factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations